THE EFFECTIVENESS OF THEORETICAL LESSONS IN PHYSICAL EDUCATION CLASSES (Scientific journal of the Fergana State University, 2025)
This article examines the effectiveness of theoretical lessons in physical education classes for high school students in general education schools. The aim of the study was to ensure deep assimilation of theoretical knowledge by students and to assess the impact of this knowledge on their overall physical preparedness. The study compared a control group and an experimental group. The control group was taught according to the standard curriculum, while the experimental group received separate theoretical lessons each quarter. The results showed that students in the experimental group effectively absorbed theoretical knowledge and successfully applied it in practical sessions. Statistical analysis was conducted using the Student's t-test, confirming the effectiveness of the experimental methodology. This article demonstrates that incorporating theoretical knowledge into physical education classes and integrating it with practical training contributes to supporting students' healthy lifestyles.